Study of thickness effects on the nonlinear of paprika oil and pepper oil - عبد الحسين مشاري جاسب; طالب عبد علي اسراء (University of Thi-Qar Journal of Science, 2017)
In this article the optical nonlinear propreties in paprika oil and pepper oil are studied using two visible laser beams a two wavelengths 532 nm and 473 nm via diffraction ring patterns. Both total change in refractive index, ∆n, and nonlinear refractive index , n2 ,has changed against samples thicknesses. The outer most ring diameter in each pattern has change a lot. It appear to us that thermal nonlinear refractive in negative. The increase of samples thicknesses and the decrease of input power reduce ∆n and n2.